Estimation of gingerol content in different brand samples of ginger powder and their anti-oxidant activity: A comparative study - Mishra, Abhay Prakash; Saklani, Sarla; Chandra, Subhash (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Gingerol is the most abundant constituent of fresh ginger has potent antioxidant activity but it decreases during postharvest storage and processing. The present work efforts have been made to estimate Gingerol content in different brand samples of Ginger powder and their antioxidant activity compared with the sample cultivated through organic farming. Organic farmed sample was collected from the FRI, Dehradun (UK), other samples were taken from the markets of Srinagar Garhwal and Dehradun and was identified from the Dept. of Botany H.N.B. Garhwal University, Srinagar Garhwal (UK). All regents and chemicals were used of analytical and HPLC grade and extraction was carried out by hot solvent extraction method. FRAP method was used for Antioxidant activity. Simple reversed-phase HPLC-UV method, with gradient elution, was used to estimate the gingerol. A typical HPLC-UV chromatogram was obtained which exhibited a clean and smooth baseline with excellent resolution where all the marker peaks could be identified and quantified. The amount of gingerol in the sample S1 is 04.54%, in S2 is 08.01%, in S3 is 06.74%, in S4 is 04.20%, in S5 is 06.74% and in S6 is 08.54%, estimated respectively by HPLC analysis. Among all samples, S6 (ginger cultivated through organic farming) has significant quantity of gingerol in comparison to other market samples.The reducing ability of different samples of ginger extracts was in the range of 368.27 ± 23.43-3107.28 ± 42.31μmol/g dry weight. The FRAP values for the methanolic extracts of rhizomes in all six varieties were significantly lower than those of vitamin C and α-tocopherol, but higher than that of BHT. When we compared all five market samples with ginger cultivated through organic farming had excellent antioxidant activity. The results conclude that ginger which cultivated through organic farming has a significant antioxidant activity and has a positive relationship between antioxidant activities and total phenolic contents. The high antioxidant activity shows the higher level of total phenolic and flavonoids.